OPTIMIZING ENERGY EFFICIENCY IN WIRELESS BODY AREA NETWORKS FOR SMART HEALTH MONITORING - Muhammad Talha Tahir Bajwa; Abdullah Yousaf; Ayesha Quyyum; Fizza Tehreem; Hafiz Muhammad Farooq Tahir; Asad Mehmood (Spectrum of Engineering Sciences, 2025)
Wireless Body Area Networks (WBANs) are rapidly emerging as a transformative component of healthcare, allowing for the seamless integration of technology and medical science to improve patient care and clinical outcomes. These networks are made up of small, intelligent, and low-power sensor nodes that are either worn on or implanted in the human body to continuously monitor physiological signals like heart rate, blood pressure, temperature, glucose levels, and so on. This study provides a full overview of the WBAN architecture, its primary components (biosensors, communication modules, and base stations), and the underlying communication protocols that allow reliable data transmission. The primary focus is on the real-time use of WBANs in health monitoring systems, which enable remote patient observation, minimize hospital visits, and assist early diagnosis and preventive care. We also investigate how WBANs improve healthcare delivery for the elderly, the chronically ill, and those living in rural places. The study also covers crucial concerns such as sensor device battery life, the necessity for secure and private data transmission, interoperability issues, and assuring data integrity and accuracy in a variety of situations. Various methods and current research trends for overcoming these issues are explored. Finally, the study discusses potential future options, such as combining WBANs with AI, Big Data analytics, and cloud computing to improve decision-making, predictive analysis, and individualized therapy. WBANs' continual evolution has the ability to profoundly transform the global landscape of digital health and smart healthcare systems.